2020
DOI: 10.1002/csc2.20122
|View full text |Cite
|
Sign up to set email alerts
|

Fine fescues: A review of the species, their improvement, production, establishment, and management

Abstract: Fine fescues (Festuca L. spp.) comprise a group of five cool-season grasses used in turfgrass systems under many conditions: strong creeping red fescue (F. rubra L. ssp. rubra Gaudin), slender creeping red fescue [F. rubra L. ssp. littoralis (G. Mey.) Auquier], Chewings fescue [F. rubra L. ssp. commutata Gaudin; syn. F. rubra L. ssp. fallax (Thuill.) Nyman], hard fescue (F. brevipila Tracey), and sheep fescue [F. ovina L.; syn. F. ovina L. ssp. hirtula (Hack. ex Travis) M.J. Wilk.]. Their extensive geographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
125
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 62 publications
(158 citation statements)
references
References 179 publications
(404 reference statements)
12
125
4
Order By: Relevance
“…At Oregon, shredded paper resulted in the slowest germination and emergence (12.6 d), whereas potting soil facilitated the fastest germination and emergence of fine fescue (Table 3). Overall, there were no clear trends across locations in the rate of seedling emergence among mulch ingredients and the number of days required until first seedling emergence ranged from 10 to 13 d in Indiana and 7 to 14 d in Oregon, which is consistent with past reports (5–12 d) (Braun et al., 2020). In comparison, Karcher and Baser (2002) reported no differences in the initial germination date of tall fescue with three mulch materials.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…At Oregon, shredded paper resulted in the slowest germination and emergence (12.6 d), whereas potting soil facilitated the fastest germination and emergence of fine fescue (Table 3). Overall, there were no clear trends across locations in the rate of seedling emergence among mulch ingredients and the number of days required until first seedling emergence ranged from 10 to 13 d in Indiana and 7 to 14 d in Oregon, which is consistent with past reports (5–12 d) (Braun et al., 2020). In comparison, Karcher and Baser (2002) reported no differences in the initial germination date of tall fescue with three mulch materials.…”
Section: Resultssupporting
confidence: 89%
“…These commercial products predominantly contain turfgrass species such as perennial ryegrass and tall fescue but little to no low‐input turfgrass species such as fine fescues (Table 1). For instance, an evaluation of products commercially available in 2019 determined the average seed mixture contained 2.2% of a fine fescue taxon, which is similar to the <1.5% fine fescue included in 2018 patch and repair products (Braun et al., 2020). As the demand to reduce water, fertilizer, and pesticide inputs rises, there will be a need for more low‐input turfgrass options, such as fine fescues (Braun et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fine-leaved fescues, or fine fescues, are a taxonomically complex group of taxa which are typically classified into one of two complexes known as the red fescue (Festuca rubra L.) complex and the sheep fescue (F. ovina L.) complex. This group of species has been thoroughly reviewed by Braun et al (2020) with regard to their taxonomy and use. The F. rubra L. sensu lato complex, native to Europe, has widespread distribution throughout Asia, North America, and Europe (Ruemmele, Wipff, Brilman, & Hignight, 2003 (Pavlick, 1985).…”
Section: Fine Fescues History and Roadside Usementioning
confidence: 99%
“…For instance, fine fescues (Festuca ssp. ), a group of lower-input turfgrasses (Braun, Patton, Watkins, Koch, Anderson, et al, 2020), have been previously shown to provide acceptable turfgrass quality and performance over more traditionally-used turfgrasses in multiple contexts including roadsides (Friell, Watkins, & Horgan, 2012), lawns (Hugie & Watkins, 2016), golf course fairways (Watkins, Hollman, & Horgan, 2010), and out-of-play golf course roughs (Cavanaugh, Watkins, Horgan, & Meyer, 2011). Colonial bentgrass (Agrostis capillaris L., CLB), an alternative bentgrass to CRB, has been tested extensively at greens height in northern Europe; Aamlid, Thorvaldsson, Enger, & Pettersen (2012) found its overall performance in trials managed at greens height in Norway and Iceland to be superior to CRB.…”
mentioning
confidence: 99%